MANAJEMEN PENGENDALIAN KUALITAS DALAM MENJAGA KONSISTENSI PRODUK KOPI ROBUSTA MENURUT PERSPEKTIF ISLAM PADA HOME INDUSTRY PENGOLAHAN KOPI X-BARUE - Samsuri Samsuri; Afria Rachmawati; Muhammad Abduh Alkhumaisi (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to provide general and Islamic knowledge related to quality control in maintaining product consistency of Robusta coffee at Home Industry X-Barue Kalibaru. The manuscript in this research can facilitate every coffee business enthusiast in implementing good quality control practices in accordance with principles taught in Islam. This research falls under the category of qualitative research, guided by the theory of Total Quality Management (TQM) with one of its generic tool elements, namely the process flow chart (flowchart), to visualize the production process comprehensively. The PDCA cycle from Edward W. Deming's development is also used as a presentation of data in the form of necessary work and evaluation. Data collection techniques were carried out through interviews and documentation, and the data were analyzed by performing data reduction, data presentation, and drawing conclusions. The results of this study indicate that the quality control and product consistency of Robusta coffee at Home Industry X-Barue Kalibaru are good and have implemented Islamic principles. Interviews, direct field observations, and existing documentation provide evidence that Islamic quality control has been implemented. Thus, the quality control and product consistency of Robusta coffee at Home Industry X-Barue Kalibaru have effectively applied Islamic principles and are suitable for similar businesses. Keywords: Quality Control, Product Consistency